2018
DOI: 10.1080/15732479.2018.1503689
|View full text |Cite
|
Sign up to set email alerts
|

Implications of subsoil-foundation modelling on the dynamic characteristics of a monitored bridge

Abstract: Implications of subsoil-foundation stiffness on the dynamic characteristics of a monitored bridge

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Such methods can be extended to directly identify structural properties using a second stage of model updating, where numerical structural model parameters are optimised to best match the predicted and measured modal behaviour. Whilst model updating has been used successfully to identify foundation properties in applications such as bridge, breakwater, and axial pile analyses [7][8][9], challenges in validating measurements, due to a lack of accurate modelling or benchmark data, have prevented implementation in directly estimating OWT foundation properties from monitored data. Whilst Anderson [10] investigated the components of a framework for OWT foundation parameter estimation, this was explored only through numerical simulation and applied to synthetically generated data.…”
Section: Introductionmentioning
confidence: 99%
“…Such methods can be extended to directly identify structural properties using a second stage of model updating, where numerical structural model parameters are optimised to best match the predicted and measured modal behaviour. Whilst model updating has been used successfully to identify foundation properties in applications such as bridge, breakwater, and axial pile analyses [7][8][9], challenges in validating measurements, due to a lack of accurate modelling or benchmark data, have prevented implementation in directly estimating OWT foundation properties from monitored data. Whilst Anderson [10] investigated the components of a framework for OWT foundation parameter estimation, this was explored only through numerical simulation and applied to synthetically generated data.…”
Section: Introductionmentioning
confidence: 99%
“…However, Mylonakis et al (2006a), Kappos & Sextos (2009) and Zheng et al (2015) found a non-negligible contribution of SSI towards inelastic structural seismic demand. Chaudhary (2017bChaudhary ( , 2018 and Faraonis et al (2019) noted that impact of SSI on structural performance and modal parameters was related to the relative stiffness of pier columns and soil-foundation system instead of properties of the supporting soil alone.…”
Section: Introductionmentioning
confidence: 99%